The Little Data Book on Africa 2008 - World Bank (The World Bank, 2008)
This book provides profiles of over 50 countries with 54 development indicators about people, environment, economy, technology, infrastructure, trade and finance, all in one handy, pocket-sized volume. A must have for anyone interested in today's development challenges in sub-Saharan Africa